Opioid use for a first-incident upper extremity fracture in 220, 440 patients without recent prior use in Ontario, Canada: a retrospective cohort study. Issue 3 (7th September 2022) - MacDermid, Joy C.; McClure, J. Andrew; Richards, Lucie; Faber, Kenneth J.; Jaglal, Susan
Abstract : Objective: To describe opioid use for a first upper extremity fracture in a cohort of patients who did not have recent opioid use. Design: Descriptive epidemiological study. Setting: Emergency Department, Hospital. Patients/Participants: We obtained health administrative data records of adults presenting with a first adult upper extremity fracture from 2013 to 2017 in Ontario, Canada. We excluded patients with previous fractures, opioid prescription in the past 6 months or hospitalization >5 days after the fracture. Intervention: Opioid prescription. Main Outcome Measurements: We identified the proportion of patients filling an opioid prescription within 7 days of fracture. We described this based on different upper extremity fractures (ICD-10), Demographics (age, sex, rurality), comorbidity (Charlson Comorbidity Index, Rheumatoid arthritis, Diabetes), season of injury, and social marginalization (Ontario Marginalization Index-a data algorithm that combines a wide range of demographic indicators into 4 distinct dimensions of marginalization). We considered statistical differences ( P < .01) that reached a standardized mean difference of 10% as being clinically important (standardized mean difference [SMD] ≥ 0.1). Results: From 220, 440 patients with a first upper extremity fracture (50% female, mean age 50), opioids were used by 34% of cases overall (32% in males, 36% in females, P< .001, SMD ≥ 0.1). Use varied by body region, with those with multiple or proximal fractures having the highest use: multiple shoulder 64%, multiple regions 62%, shoulder 62%, elbow 38%, wrist 31%, and hand 21%; and was higher in patients who had a nerve/tendon injury or hospitalization (P< .01, SMD ≥ 0.1). Social marginalization, comorbidity, and season of injury had clinically insignificant effects on opioid use. Conclusions: More than one-third of patients who are recent-non-users will fill an opioid prescription within 7 days of a first upper extremity fracture, with usage highly influenced by fracture characteristics. Level of Evidence: Level II